Hubungan Antara Self-Efficacy dan Pengetahuan Technopreneur dengan Minat Berwirausaha di Bidang Busana Peserta Didik Kelas X Tata Busana SMK Negeri 1 Jabon - Sumadyowati Awanda Erna; Lutfiyah Hidayati (Journal on Education, 2024)
The research investigates self-efficacy, technopreneur knowledge, and interest in entrepreneurship in the fashion sector among class X Fashion Design students at SMK Negeri 1 Jabon. Additionally, the study aims to explore the correlation between self-efficacy and interest in entrepreneurship in the fashion sector, technopreneur knowledge and interest in entrepreneurship in the fashion sector, and self-efficacy, technopreneur knowledge and interest in entrepreneurship in the fashion sector. The research employed a saturated sampling technique, employing questionnaire instruments and multiple-choice tests. The study's final results indicate a tendency towards high levels of self-efficacy and interest in entrepreneurship in the fashion sector among the participants. Multiple regression analysis reveals that the calculated t-values of self-efficacy and technopreneur knowledge are 7.010 and 4.453, respectively, more significant than the accepted value of 2.040 at a significance level of 0.000 <0.05. Therefore, partially, the self-efficacy variable has a relationship with interest in entrepreneurship in the fashion sector, as well as the technopreneur knowledge variable. Furthermore, the obtained F count of 192.145 is greater than the accepted value of 3.305 at a significance level of 0.000 <0.05. This indicates that simultaneously, self-efficacy and technopreneur knowledge are related to interest in entrepreneurship in fashion for class X students with 92.5% accuracy. In comparison, the remaining 7.5% is associated with other variables.